(untitled) (Baghdad Science Journal, 2019)
A study of the effects of the discharge (sputtering) currents (60-75 mA) and the thickness of copper target (0.037, 0.055 and 0.085 mm) on the prepared samples was performed. These samples were deposited with pure copper on a glass substrate using dc magnetron sputtering with a magnetic flux density of 150 gauss at the center. The effects of these two parameters were studied on the height, diameter, and size of the deposition copper grains as well as the roughness of surface samples using atomic force microscopy (AFM).The results of this study showed that it is possible to control the specifications of copper grains by changing the discharge currents and the thickness of the target material. The increase in discharge current values ​​led to a decrease in height copper grain’s values ​​of 20% at a current of 75 mA and target thickness of 0.085 mm. Furthermore, the increasing in the current caused a decrease in the diameter and size values of deposition copper grains. Finally, the surface roughness of the samples was reduced by a 15% by changing the current and target material thickness at 75 mA and 0.085mm respectively.